The Mathematics Ethnic Learning Program in Improving the Understanding of Mathematical Concepts and the Character of Homeland Love: - - Wibowo, Sigit; Unik Ambarwati; Fery Muhamad Firdaus (Universitas Pendidikan Ganesha, 2023)
Mathematics learning is still considered abstract and challenging to understand for most elementary school students. This results in students' low understanding of mathematical concepts. This research aims to measure the effectiveness of the